2022
DOI: 10.1021/acssensors.2c00135
|View full text |Cite
|
Sign up to set email alerts
|

Attomolar Sensitivity in Single Biomarker Counting upon Aqueous Two-Phase Surface Enrichment

Abstract: From longstanding techniques like enzyme-linked immunosorbent assay (ELISA) to modern next-generation sequencing, many of the most sensitive and specific biomarker detection assays require capture of the analyte at a surface. While surface-based assays provide advantages, including the ability to reduce background by washing away excess reagents and/or increase specificity through analyte-specific capture probes, the limited efficiency of capture from dilute solution often restricts assay sensitivity to the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…(c) Enhancement of mass transport of trace targets to surfaces using an aqueous two-phase system of saline (salt phase) and poly(ethylene glycol) (PEG phase) that condenses the targets to the surface. 52 concentration. Analytical challenges are greater for proteins than for nucleic acids in part due to the sheer diversity of the proteome compared with the genome, with protein isoforms, posttranslational modifications, dynamically changing conformations, and natively interacting molecules like heterophilic antibodies all potentially impacting capture efficiency by bioaffinity tags.…”
Section: Bioaffinity Tagsmentioning
confidence: 98%
See 4 more Smart Citations
“…(c) Enhancement of mass transport of trace targets to surfaces using an aqueous two-phase system of saline (salt phase) and poly(ethylene glycol) (PEG phase) that condenses the targets to the surface. 52 concentration. Analytical challenges are greater for proteins than for nucleic acids in part due to the sheer diversity of the proteome compared with the genome, with protein isoforms, posttranslational modifications, dynamically changing conformations, and natively interacting molecules like heterophilic antibodies all potentially impacting capture efficiency by bioaffinity tags.…”
Section: Bioaffinity Tagsmentioning
confidence: 98%
“…Li et al showed that an immiscible fluid can be used to concentrate attomolar nucleic acid solutions above a capture surface for digital counting, an approach that may be more amenable to simple fluidic systems (Figure 7c). 52 Gao and co-workers also observed that probe capture could be enhanced by cycling solutions above a capture surface with a gas phase through draining, which replenishes the "depletion zone" of targets in the solution proximal to the capture surface. 53 Xiong et al showed that microscopic stir bars that enhance convective transport can substantially increase capture efficiency in surface capture assays.…”
Section: Target Capture From Attomolar Solutionsmentioning
confidence: 99%
See 3 more Smart Citations